2018
DOI: 10.4103/apjon.apjon_5_18
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness, Perceived Social Support and their Relationship in Iranian Patients with Cancer

Abstract: Objective:Cancer is considered a global health problem and its prevalence has been growing in recent years. The present study was conducted to investigate the role of hopelessness and perceived social support for Iranian patients with cancer.Methods:Convenience sampling was used to select the study sample comprising 100 patients with cancer presenting to the Education and Treatment Center of Valiasr in Zanjan, Iran. A demographic questionnaire, the Beck Hopelessness Scale, and the Social Support from Family an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
5
17
3
3
Order By: Relevance
“…In line with the results of the present study, studies conducted by Alipour et al ( 40 ) on patients with type II diabetes, Madani et al ( 31 ) on Iranian patients with cancer and Taei et al ( 14 ) on patients with breast cancer revealed a positive correlation between social support and hopefulness. Pehlivan et al ( 41 ) also performed a study on Turkish cancer patients and showed a negative relationship between hopelessness and perceived familial social support.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with the results of the present study, studies conducted by Alipour et al ( 40 ) on patients with type II diabetes, Madani et al ( 31 ) on Iranian patients with cancer and Taei et al ( 14 ) on patients with breast cancer revealed a positive correlation between social support and hopefulness. Pehlivan et al ( 41 ) also performed a study on Turkish cancer patients and showed a negative relationship between hopelessness and perceived familial social support.…”
Section: Discussionsupporting
confidence: 92%
“…The role of perceived social support in spiritual intelligence and hope has been evaluated, as well. The results of the studies conducted by Alipour et al in patients with type II diabetes ( 40 ), Madani et al in Iranian patients with cancer ( 31 ), Taei et al ( 14 ) and Pehlivan et al ( 41 ) in patients with breast cancer showed a positive correlation between social support and hopefulness. Dehbashi et al ( 30 ) also revealed a significant positive relationship between hope and spiritual well-being.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…36 Accordingly, increase in social support by families could reduce despair in patients with chronic diseases, such as cancer. 37 As mentioned before, social support has been reported to be associated with health in patients with chronic diseases. Peer support was also associated with self-care in patients with diabetes.…”
Section: Introductionmentioning
confidence: 87%